PENAFSIRAN MAKNA LAGU TRADISIONAL BATAK TOBA ANDUNG “SAUR MATUA MAHO INANG” (ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE) - Julyo Armando Hugo; Ilona Situmeang (SEMIOTIKA: Jurnal Komunikasi, 2016)
The purpose of this study to determine the interpretation of the meaning contained in the lyrics of the song "Saur Matua Maho Host". The lyrics of this song tells the outpouring child to his mother who died. The contents of each sentence was the outpouring of touching hearts for music listeners who listen to the song Batak song. This study uses the Semiotics Ferdinand de Saussure. In semiotic divided into five elements, namely the signifier (the marker) and the signified (signified), Form (form) and content (content), Langue (language) and parole (speech / speech), synchronic (synchronous) and diachronic (diachronic), Syntagmatic (syntagmatic) and associative (paradigmatic). Each element has a deep meaning. The method used qualitative descriptive research and constructivism. The unit of analysis is the study of the object to be analyzed, namely lyrics grandmother "Saur Matua Maho Host". From the results of the interpretation of this song, it can be seen that the lyrics "Saur Matua Maho Host" tells the outpouring who want disclosed to the mother who had died. All the lyrics of the song contains acknowledgments child to his mother who had raised him to be successful. This song is usually always sung by a daughter who will be sung when her mother's funeral.Keywords: Interpretation, Meaning Songs and Semiotics Saussure.